Evaluation of specific lipid production and nutrients removal from wastewater by Rhodosporidium toruloides and biodiesel production from wet biomass via microwave irradiation. (1st August 2016) - Ling, Jiayin; Nip, Saiwa; de Toledo, Renata Alves; Tian, Yuan; Shim, Hojae
Abstract: This study investigated the potential use of yeast Rhodosporidium toruloides for lipid production and removal of organics and nutrients while treating a mixture of distillery and domestic wastewater at low cost without sterilization. The highest specific biomass (24.1 × 10 −9 g L −1 cell −1 h −1 ), lipid yield (9.9 × 10 −9 g L −1 cell −1 h −1 ), and lipid content (8.54 × 10 −3 g lipid g −1 biomass h −1 ) were achieved on the 2nd day of cultivation. The organics and nutrients removal also reached the highest removal rates within 2 days, with the specific removal rates for COD (chemical oxygen demand), TN (total nitrogen), and TP (total phosphorus) at 39.5, 2.57, and 0.29 × 10 −9 mg cell −1 h −1, respectively. The indigenous microorganisms slightly contributed to both lipid production and removal of organics and nutrients. The direct transesterification process via microwave irradiation from wet biomass was further optimized under the conditions of solvent to wet biomass rate 16 mL/g, methanol and chloroform mix rate 1:1, addition of catalyst H2 SO4 6%, and reaction time 10 min at the reaction temperature of 60 °C. The FAMEs (fatty acid methyl esters) composition and the possibility of biodiesel production from wet oleaginous yeast biomass by the direct transesterification were also assessed. Highlights: Yeast Rhodosporidium toruloides used for lipid production in real mixed wastewater. No significant lipid production and nutrients removal by indigenous organisms. Highest specific lipid production and nutrient removal rates achieved with 0.05 × 10 8 cells mL −1 . Biodiesel production from wet biomass via microwave assisted direct transesterification is feasible.